Diagnóstico y propuesta de un manual de seguridad y salud ocupacional para el talento humano del Gad del cantón Chinchipe en la ciudad de Zumba, provincia de Zamora Chinchipe, para el año 2016 - Cueva Ochoa, Olga Piedad (2017)
The present investigation was called "DIAGNOSIS AND PROPOSAL OF A MANUAL OF SAFETY AND OCCUPATIONAL HEALTH FOR THE HUMAN TALENT OF GAD OF CANTÓN CHINCHIPE IN THE CITY OF ZUMBA, PROVINCE OF ZAMORA CHINCHIPE, FOR THE YEAR 2016", had as general objective to evaluate The situation of human talent and propose a manual of occupational health and safety for the year 2017. The methods used were: analytical that allowed to determine the requirements to propose the manual of occupational health and safety, with inductive method the labor risks of the entity were analyzed, deductive was used to establish concept to design the manual, bibliographic scientific data was collected for The development of research, and statistics served to analyze and interpret the results of the survey applied. Techniques such as: direct observation that allowed to examine the current situation of human talent GAD canton Chinchipe, survey of 111 employees working in the public institution, to obtain information on occupational health and safety. For the development of investigative work, a direct observation sheet was used to obtain data on work risks. A survey was also carried out on workers in order to know about the hazards in the work environment, information to design a proposal for improvement. With the procedure applied, it was possible to identify the positions that present the highest occupational health risks, being these: the mayor demonstrates a pressure of the charge for the enormous amount of responsibility, the workshop boss due to the manipulation of load, noise, Contamination agents, as well as positions of warehouse manager, warehouse keeper, warehouse assistant, mechanic present mechanical hazards due to the fall of manipulable objects, blows, unprotected machinery among others. While the positions of commissioner, prosecutor, accountant, collector, are exposed to risks of stress due to interaction with problematic persons, due to the excessive burden of responsibility that he has before his duties, and finally the veterinarian demonstrates biological risks because they do not have a well-equipped laboratory. In reference to the obtained results, it was established as a proposal to design a manual of occupational health and safety for the human talent of the Autonomous Government Decentralized municipal of the canton Chinchipe. Finally, it was determined as a relevant conclusion that this manual is designed according to the needs and requirements of the human talent of the municipal GAD of the Chinchipe canton with the purpose of improving the work environment, to obtain greater efficiency in the provision of service to the citizenship Of Zumba.